Gambaran Diferensiasi Sel Darah Putih Tikus (Ratitus norvegicus) Betina Pada Starvasi - Safrida Safrida (Universitas Syiah Kuala, 2010)
Starvation causes food and liquid deficit that needed by body. Percentage differential leukocyte count includes neutrophil, eosinophil, basophil, limphosit and monosit will give indication towards infection reaction. The aim of this research is to detect influence starvation of the description differential leukocyte count in adult female rat during certain range of time. The experimental method used in this research is Randomized complete design with 3 blocks of treatments and 3 times repetition. The block of treatments are control (K), fasting eat rats (PMK), fasting drink rats (PMN). The data of percentage differential leukocyte count is analyzed by Analysis of Variance (ANOVA) and then continued by Duncan Multiple Range Test at 95% confidence interval (5% significance level). The result showed that statistically insignificant percentage of limphosit, neutrophil, and monosit in PMK and PMN bloks when compared with control, and basophil was not found. While, treatment PMK and PMN in 18 hours treatment, 42 hours treatment, and 66 hours treatment increase percentage eosinophil.